An evidence-based socioecological framework to understand men's use of anabolic androgenic steroids and inform interventions in this area. (2nd November 2019) - Bates, Geoff; Tod, David; Leavey, Conan; McVeigh, Jim
Abstract: Research into men's use of anabolic androgenic steroids (AAS) over the past three decades has identified many factors that contribute to decision-making in this area. However, there are limited theoretical frameworks to synthesise this research and guide practice, such as interventions to prevent use or reduce health risks. To address this gap, a socioecological framework is presented based upon the international literature examining AAS use. Socioecological models recognise that individuals and behaviours exist within complex physical and social systems and are useful tools for guiding interventions to ensure consideration is given to multiple influential factors. This framework proposes that use of AAS is the result of the interaction of a range of factors at the individual, social network, institutional, community, and societal levels that are likely to change over time and with experience. Viewed through this framework, it becomes clear that AAS use can be a complex behaviour with many influential environments and relationships impacting on a diverse population in different ways and at different times. The implications of findings for engaging with people who use AAS and delivering interventions are discussed, such as the identification of important transition times and influencing norms within social groups and communities.